Know More Metaverse as The Technology of The Future - M F N Amirulloh; M Mulqi (International Journal of Research and Applied Technology (INJURATECH), 2022)
Technology is a science that refers to aspects of the skills to create innovations, ranging from tools to methods aimed at processing to help solve various human problems. Technology has a great influence on the progress of science and technology. The impact of the Internet and social networks is that the number of Internet users is increasing every time. With the development of technology, Internet users no longer need to meet in person to communicate. Technology is one of the main factors affecting human civilization, each time there are various technological developments, this will affect people's habits when using the Internet. One of the technological achievements of the Internet is the Metaverse technology, Internet users can interact easily and quickly. and safe. It is predicted that the development of metaverse technology will be the future of the Internet. Metaverse itself is a combination of several elements of technology, including virtual reality, augmented reality, and video, where Internet users will live in a digital world in the near future. The Metaverse is an endless digital world that is interconnected and can be used by users to work, make sales transactions, build cities, watch shows and games. The Metaverse is the first step towards realizing the digital world of business in the future.